Crystal structure of tetrasodium tetraselenidosilicate(IV), Na4SiSe4 - Preishuber-Pflügl H.; Klepp K. O. (Zeitschrift für Kristallographie - New Crystal Structures, 2003)
Na4Se4Si, orthorhombic, Pnma (No. 62), a = 14.182(5) Å, b = 9.208(3) Å, c = 7.122(3) Å, V = 930.0 Å3, Z = 4, Rgt(F) = 0.066, wRref(F) = 0.059, T = 294 K.